2000
DOI: 10.1126/science.290.5492.806
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coupling Between Meiotic DNA Replication and Recombination Initiation

Abstract: During meiosis in Saccharomyces cerevisiae, DNA replication occurs 1. 5 to 2 hours before recombination initiates by DNA double-strand break formation. We show that replication and recombination initiation are directly linked. Blocking meiotic replication prevented double-strand break formation in a replication-checkpoint-independent manner, and delaying replication of a chromosome segment specifically delayed break formation in that segment. Consequently, the time between replication and break formation was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
249
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(265 citation statements)
references
References 23 publications
11
249
1
4
Order By: Relevance
“…These results indicate that the distribution of Spo11 to later replicating regions would be coupled to DNA replication-related processes. This is consistent with previous observations that the Spo11-dependent chromatin alterations, DSB formation and DNA replicationrelated processes are tightly coupled (Borde et al, 2000;Murakami et al, 2003;Sasanuma et al, 2008;Wan et al, 2008). One possible mechanism for such coupling is that the Spo11-containing DSB machineries may migrate with the active DNA replication forks.…”
Section: Dynamic Distributions Of Spo11 Along Meiotic Yeast Chromosomessupporting
confidence: 93%
“…These results indicate that the distribution of Spo11 to later replicating regions would be coupled to DNA replication-related processes. This is consistent with previous observations that the Spo11-dependent chromatin alterations, DSB formation and DNA replicationrelated processes are tightly coupled (Borde et al, 2000;Murakami et al, 2003;Sasanuma et al, 2008;Wan et al, 2008). One possible mechanism for such coupling is that the Spo11-containing DSB machineries may migrate with the active DNA replication forks.…”
Section: Dynamic Distributions Of Spo11 Along Meiotic Yeast Chromosomessupporting
confidence: 93%
“…Borde et al (13) showed that delaying the replication of a chromosome segment specifically delays the formation of the break at that segment. Cha et al (14) showed that Spo11, which is required for interhomolog interaction, and Rec8, a meiosisspecific cohesin subunit, are negative and positive regulators for the progression of premeiotic S-phase, respectively.…”
mentioning
confidence: 99%
“…A high level of homologous recombination occurs after meiotic DNA replication but before the first meiotic nuclear division (1,(3)(4)(5)(6)(7). Meiotic recombination is required for the proper segregation of homologs at meiosis I, because a chromatid of one homolog recombines with a chromatid of the other homolog, thereby joining homologous chromosomes.…”
mentioning
confidence: 99%
“…In addition, it has been reported that the removal of active replication origin delays both replication and DSB appearance in budding yeast (5). However, in fission yeast, DSB formation occurs when completion of DNA replication is prevented by the inactivation of initiators of DNA replication (15).…”
mentioning
confidence: 99%